2001
DOI: 10.1177/144078301128756193
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Commonality in National Identities: An Exploratory Analysis of Cross-National Patterns

Abstract: Issues of boundary maintenance are implicit in all studies of national identity. By definition, national communities consist of those who are included but surrounded (literally or metaphorically) by those who are excluded. Most extant research on national identity explores criteria for national membership largely in terms of official or public definitions described, for example, in citizenship and immigration laws or in texts of popular culture. We know much less about how ordinary people in various nations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(196 citation statements)
references
References 10 publications
8
184
2
2
Order By: Relevance
“…Sociologists have shown that ethnic elements of national identity hold more salience for individuals across nations than do civic elements (Jones & Smith, 2001), but that individuals of minority backgrounds favor civic elements (Kunovich, 2009). Individual teachers, therefore, may emphasize elements of the written curriculum or introduce content and perspectives from outside the textbooks based on those elements of national identity most meaningful to them.…”
Section: Research Approachmentioning
confidence: 99%
“…Sociologists have shown that ethnic elements of national identity hold more salience for individuals across nations than do civic elements (Jones & Smith, 2001), but that individuals of minority backgrounds favor civic elements (Kunovich, 2009). Individual teachers, therefore, may emphasize elements of the written curriculum or introduce content and perspectives from outside the textbooks based on those elements of national identity most meaningful to them.…”
Section: Research Approachmentioning
confidence: 99%
“…L'autre conception (ethnique ou objectiviste) repose davantage sur des notions objectives de parenté et de culture, par exemple le fait tout simplement d'être né au Vanuatu ou bien de parler couramment le bislama, de respecter la kastom ou de se déclarer chrétien. Enfin, notre enquête permet d'examiner en une mesure générale comment les attitudes et les croyances sur l'identité nationale peuvent se transposer dans les politiques instaurées au niveau institutionnel et se transmettre dans la mythologie collective et les discours publics (Jones et Smith, 2001). …”
Section: Questions De L'identité Nationale Depuis L'indépendanceunclassified
“…Ethnic criteria such as having national ancestry or being a member of the main religious group of the nation are hard or impossible to obtain. On the other hand, civic criteria entail a voluntarist representation of the nation (Jones & Smith, 2001), where being a member of the nation requires adherence to political and cultural aspects of the nation (e.g., respecting institutions and speaking the language). Because they can be acquired, civic criteria might appear to be less strict than ethnic criteria.…”
Section: Conceptions Of Nationhoodmentioning
confidence: 99%